Bio‐Inspired Bright Structurally Colored Colloidal Amorphous Array Enhanced by Controlling Thickness and Black Background. Issue 26 (26th April 2017) - Iwata, Masanori; Teshima, Midori; Seki, Takahiro; Yoshioka, Shinya; Takeoka, Yukikazu
Abstract : Inspired by Steller's jay, which displays angle‐independent structural colors, angle‐independent structurally colored materials are created, which are composed of amorphous arrays of submicrometer‐sized fine spherical silica colloidal particles. When the colloidal amorphous arrays are thick, they do not appear colorful but almost white. However, the saturation of the structural color can be increased by (i) appropriately controlling the thickness of the array and (ii) placing the black background substrate. This is similar in the case of the blue feather of Steller's jay. Based on the knowledge gained through the biomimicry of structural colored materials, colloidal amorphous arrays on the surface of a black particle as the core particle are also prepared as colorful photonic pigments. Moreover, a structural color on–off system is successfully built by controlling the background brightness of the colloidal amorphous arrays. Abstract : Inspired by Steller's jay, which displays angle‐independent structural colors, angle‐independent structurally colored materials that are composed of amorphous arrays of sub‐micrometer‐sized fine spherical silica colloidal particles are created by the layer‐by‐layer method on a black plate.